PENGEMBANGAN BAHAN AJAR MODUL ILMU PENGETAHUAN ALAM KELAS IV DI SDN 3 REMPUNG - Zalwa Nadia; Donna Boedi Maritasari; Rohini Rohini (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
This study aims to develop a science module as material for learning activities, especially in science subjects using the Borg and Gall research model which consists of 10 steps simplified into 7 steps, namely (1) conducting a needs analysis, (2) planning, (3) initial product development, (4) limited testing, (5) revision of product test results, (6) main product test, (7) final product revision. This study was conducted on class IV students with a total of 22 students. This research and development instrument uses validation sheets and student response questionnaires. The results of the media design expert validation test with a total score of